Asymptomatic left circumflex artery stenosis is associated with higher arrhythmia recurrence after persistent atrial fibrillation ablation - Garcia, Rodrigue; Clouard, Mathilde; Plank, Fabian; Degand, Bruno; Philibert, Séverine; Laurent, Gabriel; Poupin, Pierre; Sakhy, Saliman; Gras, Matthieu; Stühlinger, Markus; Szegedi, Nándor; Herczeg, Szilvia; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The pathophysiology of persistent atrial fibrillation (AF) remains unclear. While several studies have demonstrated an association between myocardial infarction and atrial fibrillation, the role of stable coronary artery disease (CAD) is still unknown. As a result, we aimed to assess the association between CAD obstruction and AF recurrence after persistent AF ablation in patients with no history of CAD. Methods: This observational retrospective study included consecutive patients who underwent routine preprocedural cardiac computed tomography (CCT) before persistent AF ablation between September 2015 and June 2018 in 5 European University Hospitals. Exclusion criteria were CAD or coronary revascularization previously known or during follow-up. Obstructive CAD was defined as luminal stenosis ≥50%. Results: All in all, 496 patients (mean age 61.8 ±10.0 years, 76.2% males) were included. CHA2DS2-VASc score was 0 or 1 in 225 (36.3%) patients. Obstructive CAD was present in 86 (17.4%) patients. During follow-up (24 ±19 months), 207 (41.7%) patients had AF recurrence. Recurrence rate was not different between patients with and without obstructive CAD (43.0% vs. 41.5% respectively; P=0.79). When considering the location of the stenosis, recurrence rate was higher in case of left circumflex obstruction: 56% vs 32% at 2 years (log-rank P<0.01). After Cox multivariate analysis circumflex artery obstruction (HR 2.32; 95%CI 1.36 - 3.98; P<0.01) was independently associated with AF recurrence. Conclusions: Circumflex artery obstruction detected with CCT was independently associated with 2- fold increase in risk of AF recurrence after persistent AF ablation. Further research is necessary to evaluate this pathophysiological relationship.